(3VeGfGJ GdGSJKeGQ aj GdOhd GdYQHjI (B:s (3OQGSI bGfhfjI ebGQfI dCge GdJTQjYGJ GdYQHjI hGdeYGgOGJ GdOhdjI eY GdETGQI Edi efXeI GdJLGQI GdYGdejI hOhQgG aj gPG GdeLGd (B/s - (3YHO Gddg, YHO Gddg YHO GdcQje eMeOs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2010)
(3jJfGhd cJGH (B((3VeGfGJ GdGSJKeGQ aj GdOhd GdYQHjI (B: (3OQGSI bGfhfjI ebGQfI dCge GdJTQjYGJ GdYQHjI hGdeYGgOGJ GdOhdjI eY GdETGQI Edi efXeI GdJLGQI GdYGdejI hOhQgG aj gPG GdeLGd(B) (3hGdPj bGe HJCdjag (B((3YHO Gddg YHO GdcQje YHO Gddg(B) (3aj MhGdj (B(223) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdGSJKeGQGJ(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdebOeI, GdaUd GdChd (B: (3eaghe VeGfGJ GdGSJKeGQ hCfhGYgG hCgejJgG hETcGdjJgG hfWGbgG, GdaUd GdKGfj (B: (3VeGfGJ GdGSJKeGQ GdOGNdjI aj HYV JTQjYGJ GdOhd GdYQHjI, GdaUd GdKGfj (B: (3VeGfGJ GdGSJKeGQGJ GdOhdjI ef GdfGMjI GdbGfhfjI, GdaUd GdKGdK (B: (3VeGfGJ GdGSJKeGQGJ GdOhdjI ef GdfGMjI GdGbJUGOjI(B.s
(3HHdjhLQGajI (B: (3UaMI (B213-223.s
Keywords: World Trade Organization; (3GdGSJKeGQGJs -- (3bhGfjf hJTQjYGJs -- (3GdHdGO GdYQHjIs